The Effect of the Type of Screw Fixation Used in the Treatment of Slipped Capital Femoral Epiphysis - Tyler Rudolph; Katie Rooks; Haemish Crawford; Michael van der Merwe (Advances in Orthopedics)
Background. Slipped capital femoral epiphysis (SCFE) remains among the most common hip disorders in the adolescent population. The management of SCFE remains controversial; however, the aim of fixation is to stabilize the physis and prevent further slippage. In situ fixation remains the gold standard; however, in the young population, it can lead to reduced femoral neck growth and complications such as leg length discrepancies. The ideal form of in situ fixation for mild to moderate SCFE would stabilize the slip and allow continued proximal femoral growth. This study aimed to determine if partially threaded screws allowed more neck growth than fully threaded screws. Methods. A retrospective review of the radiographs of all patients undergoing in situ fixation for SCFE using partially threaded and fully threaded screws. Measurements included neck length, neck-to-screw ratio, neck shaft angle, neck width, and articular-trochanteric distance. Parameters were compared over a two-year period to determine whether there was any difference in proximal femoral growth between the two types of screws. Results. Fully threaded screw neck length increased by 5 mm versus 5 mm for proximally threaded screws (P≤0.001). No significant difference was observed between the two groups with respect to neck width, neck shaft angle, and articular-trochanteric distance. Conclusions. No difference was observed in proximal femoral growth. Regardless of which type of fixation is used, neck length continues to increase by approximately 3 mm per year.